Implemantation of Kampung KB in Increasing Community Self-Help at Kampung KB Kecamatan Nagrak Kabupaten Sukabumi - Ilva Maidia Wita (Universitas Negeri Padang, 2019)
The slow decline in fertility rates (TFR) and the weakening of the implementation of the program for Population, Family Planning and Family Development (KKBPK) at the level of the field lines at the moment, so it will need a strategic innovation program to strengthen KKBPK 2015-2019 program that has leverage the efforts to achieve the target / targets as well as expand the scope of the cultivation program at all levels KKBPK West Java Province through the family planning construck program. Family planning construck in design as a community empowerment efforts of the management of family planning programs. Its activities are managed based on the principle of, by, and for the community itself, as an end of course the development of society itself. The government only stimulate and mentoring, the rest is the responsibility of society. With the approach of qualitative research study conducted by applying the stages of operational research in order to evaluate the success of the intervention program in family planning construck at Nagrak, Sukabumi regency. The purpose of this study to improve the achievement KKBPK program and other related programs to mewujudkaan quality small family. The research results are the success of the family planning construck is largely determined by the active role of the family or the community in various levels, to the need for intervention programs, funds, facilities, infrastructure, IEC, advocacy, mobilization and facilitation of SKPDKB and across sectors with the final target culture movement collectively and sustainable, the village family planning can be considered as a public initiative is not just a government program. Regent crucial role together Working Group Family planning construck Regency / City by involving members of parliament sit with an agenda intervention program in the family planning construck as well as to maintain the continuity of the program. Necessary assistance in the implementation of the program KKBPK field line and training